Income and wealth as salient gradational aspects of stratification - David Brady (Luxembourg Income Study (LIS), 2022)
This chapter argues income and wealth are two paramount gradational measures of social stratification. The chapter makes this case while reviewing recent social science on income and wealth. First, I begin by explaining how income and wealth are essential for purchasing well-being. Second, I review the definition and measurement of income and wealth. This section is particularly critical because one of my overarching themes is that measurement is absolutely essential to studying income and wealth. Unfortunately, the field of social stratification - especially within the U.S. - has arguably problematically neglected measurement. Along the way, I provide empirical evidence demonstrating that measurement critically influences estimates of levels of inequality, intergenerational mobility, proxies for permanent income, and levels and trends in racial inequality. Third, I describe the levels of inequality in income and wealth. Fourth, I describe the intergenerational inheritance of or mobility in income and wealth. Fifth, I show how income and wealth outperform other measures of social class as proxies of longer term resources, such as permanent income. Sixth, I demonstrate how income and wealth matter to stratification partly because they are mechanisms for other salient inequalities, including especially racial inequalities.
Keywords: 330